Vilfredo Pareto’s sociology in his letters to Maffeo Pantaleoni - BOBBIO, N. (PSL Quarterly Review, 2014)
The article is part of a special issue on occasion of the publication of the entire scientific correspondence of Vilfredo Pareto with Maffeo Pantaleoni. It considers in particular Pareto’s main sociological work. Pareto’s sociology is indeed special as roughly three quarters of his main works deal with methodological and introductory themes, drawing a general theory of human action in a broad philosophical sense. JEL: B31, Z13